2014
DOI: 10.1103/physreve.89.052105
|View full text |Cite
|
Sign up to set email alerts
|

DNA viewed as an out-of-equilibrium structure

Abstract: The complexity of the primary structure of human DNA is explored using methods from nonequilibrium statistical mechanics, dynamical systems theory and information theory. The use of chi-square tests shows that DNA cannot be described as a low order Markov chain of order up to r = 6. Although detailed balance seems to hold at the level of purine-pyrimidine notation it fails when all four basepairs are considered, suggesting spatial asymmetry and irreversibility. Furthermore, the block entropy does not increase … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 72 publications
3
30
0
Order By: Relevance
“…In particular, regarding strand asymmetry we develop a different view than the one usually adopted in the literature. Specifically, as argued in a recent work by the present authors (Provata et al, 2014), spatial asymmetry is probed in single DNA strands and is found to give different information content when read from left-to-right than from right-to-left, indicating that DNA chromosomes can be regarded as out-of-equilibrium structures. It must be noted that the difference in the A and T content (or the C and G one) is not identical with the asymmetry produced in the reading sense.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…In particular, regarding strand asymmetry we develop a different view than the one usually adopted in the literature. Specifically, as argued in a recent work by the present authors (Provata et al, 2014), spatial asymmetry is probed in single DNA strands and is found to give different information content when read from left-to-right than from right-to-left, indicating that DNA chromosomes can be regarded as out-of-equilibrium structures. It must be noted that the difference in the A and T content (or the C and G one) is not identical with the asymmetry produced in the reading sense.…”
Section: Introductionmentioning
confidence: 87%
“…In parallel, interesting correlations related to the presence of the CpG islands were discovered (Arneodo et al, 2011;Polak and Arndt, 2009;Li and Miramontes, 2006;Zhang and Chen, 2005;Freudenberg et al, 2009;Li and Holste, 2005;Clement and Arndt, 2011;Carpena et al, 2011) and their occurrence was connected with the central role of the CG complex as a structural element of the promoter sequences (Katsaloulis et al, 2006(Katsaloulis et al, , 2009. Long range correlations were further demonstrated in the word frequency (Ebeling and Nicolis, 1991), in the information content (Roman-Roldann et al, 1996;Provata et al, 2014), in the size distribution of noncoding sequences (Almirantis and Provata, 1999), in the distribution of repeats (Massip and Arndt, 2013) and in the persistence and antipersistence of symbols (Almirantis and Provata, 1999;Melnyk et al, 2005;Zhou et al, 2004;Marx et al, 2006). Strand asymmetry has also been studied extensively in DNA literature, in the sense of a departure from intrastrand equifrequency between the A and T nucleotides and the C and G ones (Elson and Chargaff, 1952;Rudner et al, 1968;Lobry, 1996;Francino and Ochman, 1997).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…This quantity, which is often called information Shannon entropy, is studied to characterize the complexity of DNA symbolic sequences in various biological organisms [56][57][58]. The overall disorder per nucleotide is observed to vary from the value D(α) ≃ 1.339 assuming the sequence α is a first-order Markov chain, down to D(α) ≃ 1.273 if α is a 8 th -order Markov chain, which suggests the existence of long-range correlations besides the fact that the four nucleotides occur with unequal probabilities in typical DNA sequences [57,58]. In the present paper, the template is supposed to be a Bernoulli chain with equal probabilities ν 1 (n) = It should be pointed out that the sequence carries information to the extent that it is replicated, transcripted, or translated into proteins in living organisms.…”
Section: Thermodynamics and Sequence Disordermentioning
confidence: 99%